195k views
24 votes
Expand. (y^2 + 6)(-2y^2 + 7) =

2 Answers

5 votes

Answer:

-2y⁴ - 5y² + 42

Explanation:


(y^2 + 6)(-2y^2 + 7)


\mathrm{Apply\:FOIL\:method}:\quad \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd

Here First terms are

y^2 \textrm{ and } -2y^2\\(y^2)(-2y^2) = -2y^4

Outer terms are y² and 7 ==> (y²)(7) = 7y²

Inner terms are 6 and -2y² ==> 6(-2y²) = -12y²

Last terms are 6 and 7 ==> 6.7 = 42

So result is obtained by adding all these terms

-2y⁴ + 7y² - 12² + 42 ==> -2y⁴ - 5y² + 42

User Pruivo
by
5.7k points
12 votes


\: \: \: \: \: \: \: \: \: \: \: \large\underline{\bf{ANSWER}}


\: \: \: \: \: \: \: \: \: \:


\tt↠(y^2+6)(−2y^2+7)


\tt↠(-2y^2+7)y^2+6(-2y^2+7)


\tt↠-2y^4+7y^2+6(−2y^2+7)


\tt↠-2y^4+7y^2-12y^2+42


\tt↠-2y^4-5y²+42

User Maziyar Mk
by
5.9k points